Optimization of asset confiscation in prevention and eradication of money laundering - Tute, Cahyani (Journal of Law Science, 2025)
Transnational money laundering threatens economic stability and national security. One effective way to end this crime is to confiscate assets to stop the flow of criminal cash and prohibit their utilization. However, legal complexity, technological asset tracking hurdles, institutional coordination issues, and international collaboration issues hinder asset seizure in Indonesia. The lack of openness and accountability in seized asset management damages the state and lowers public faith in the judicial system. This work analyzes the asset confiscation mechanism specified in Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering and other associated laws using a normative legal research technique with a descriptive and juridical-analytical approach. As well as the Money Laundering Law and the Criminal Procedure Code (KUHAP), this research uses literature, periodicals, and comparative analysis with foreign legal systems. This research optimizes asset confiscation and identifies legal, technological, and administrative barriers. The analysis found that although the legislative foundation is appropriate, its execution is difficult. Weak law enforcement cooperation, technical limits in asset monitoring, and legal loopholes that produce variations in the reverse burden of evidence principle hinder asset confiscation. Additionally, inadequate asset management repeatedly costs the state money. To improve asset management transparency and accountability, legislative modifications, cross-institutional and international collaboration, and contemporary technology are required.